A study on the structural stability of the Asinelli Tower in Bologna. Issue 4 (28th September 2015) - Carpinteri, Alberto; Lacidogna, Giuseppe; Manuello, Amedeo; Niccolini, Gianni
Summary: This study concerns the structural stability of the Asinelli Tower in Bologna. This building is the tallest and, with the Garisenda Tower, the most undisputed symbol of the City of Bologna. The stability conditions of the tower were analyzed by means of the Acoustic Emission technique. Specifically, this approach was used to analyze the influence of repetitive and impulsive events of natural or anthropic origin, such as earthquakes, wind, or vehicle traffic on the damage evolution of the tower. Copyright © 2015 John Wiley & Sons, Ltd.